ФОРМУВАННЯ ТВОРЧОГО МИСЛЕННЯ УЧНІВ (Педагогіка вищої та середньої школи, 2003)
The article is devoted to the task o f development of pupils’ creativethinking. The author notes the special significance o f this problem under present conditions of society progress. Further the incorrectness o f stereotype approaches to the understanding o f the intellectual creation s function fo r form ing o f pupils' thinking culture is analysed. Conception “creative abilities ” and their structure in psychological & pedagogical literature is examined. Then the author lays stress on the necessity to use modern pedagogical methods & means wider and to elaborate new ones fo r development of pupil s thinking culture and creative qualities of his personality.